Diagnostic assessment for the biological sciences : development of a concept inventory : final report. - Wright, Tony; Hamilton, Susan (Australian Learning and Teaching Council, 2011)
The project team developed a set of key concepts which underpin undergraduate students understanding of the molecular world, and converted these into a web-based assessment tool the concept inventory that tests these concepts. The inventory is intended to influence pedagogical practice and knowledge and can be used by educators from a range of disciplines. Additional resources for teachers and students are available from the website. The appendices contain: a concept inventory designed to diagnose students understanding of fundamental concepts in chemistry and biology; an analysis of the key concepts underlying the inventory; a framework of big conceptual ideas for educators developing curricula in biochemistry; and a teacher resource package. -- ALTC website.